2013
DOI: 10.1155/2013/710972
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-TOF-MS Characterization and Identification of Bioactive Iridoids inCornus masFruit

Abstract: Cornus mas L. is indigenous to Europe and parts of Asia. Although Cornus is widely considered to be an iridoid rich genera, only two iridoids have been previously found in this plant. The lack of information on taxonomically and biologically active iridoids prompted us to develop and optimize an analytical method for characterization of additional phytochemicals in C. mas fruit. An ultra performance liquid chromatography (UPLC) coupled with photodiode array spectrophotometry (PDA) and electrospray time-of-flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
2
60
1
5
Order By: Relevance
“…Secoiridoids are believed to be even more advanced due to the more complicated biostynthetic steps (Xiang et al, 1996). Thus, the most closely related in the iridoids transformation pathway compounds, such as loganin ( 1 ), loganic acid ( 3 ), cornin ( 4 ), sweroside ( 5 ), and representative of secoiridoids, cornuside ( 6 ), have been detected both in fruits of C. mas and C. officinalis (Deng et al, 2013; Ma et al, 2014; Perova et al, 2014; Sochor et al, 2014; Kucharska et al, 2015; Jiang et al, 2016). However, it should be noted that in the 26 cultivars of C. mas it was shown that the most abundant iridoid was loganic acid ( 3 ) (81.5–461.1 mg/100 g fw) constituting 88–96% of total iridoids (86.9–493.7 mg/100 g fw).…”
Section: Similarities and Differences In The Chemical Composition Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Secoiridoids are believed to be even more advanced due to the more complicated biostynthetic steps (Xiang et al, 1996). Thus, the most closely related in the iridoids transformation pathway compounds, such as loganin ( 1 ), loganic acid ( 3 ), cornin ( 4 ), sweroside ( 5 ), and representative of secoiridoids, cornuside ( 6 ), have been detected both in fruits of C. mas and C. officinalis (Deng et al, 2013; Ma et al, 2014; Perova et al, 2014; Sochor et al, 2014; Kucharska et al, 2015; Jiang et al, 2016). However, it should be noted that in the 26 cultivars of C. mas it was shown that the most abundant iridoid was loganic acid ( 3 ) (81.5–461.1 mg/100 g fw) constituting 88–96% of total iridoids (86.9–493.7 mg/100 g fw).…”
Section: Similarities and Differences In The Chemical Composition Of mentioning
confidence: 99%
“…Cornuside ( 6 ) has already followed loganic acid ( 3 ) but its content was much lower than loganic acid ( 3 ) and maximally reached 36.2 mg/100 g fw (West et al, 2012a; Kucharska et al, 2015). Only two reports describe the identification of loganin ( 1 ) and sweroside ( 5 ) in fruit of C. mas (Deng et al, 2013; Perova et al, 2014). Nevertheless, the reason of limited data on identification of loganin and sweroside in fruits of cornelian cherry is due to their low concentration compared to loganic acid.…”
Section: Similarities and Differences In The Chemical Composition Of mentioning
confidence: 99%
“…Previous studies on chemical constituents of the fruits of C. mas 31 reported the isolation of anthocyanins (Du and Francis, 1973a,b;32 Seeram et al, 2002;Tural and Koca, 2008), flavonoids (Pawlowska 33 et al, 2010), iridoids (Deng et al, 2013) and carboxylic acids 34 (Krivoruchko, 2014). Our preliminary study on the C. mas fruit 35 extract using various cancer cells such as lung, prostate, cervical 36 and hepatic cancer cells showed significant cytotoxicity and 37 antibacterial study against pathogenic bacteria, Staphylococcus 38 aureus and Pseudomonas aeruginosa showed good antibacterial 39 activity.…”
Section: Q2mentioning
confidence: 98%
“…In the case of the primary metabolites, shikimic acid (2), gallic acid (3), arabinose (16), fructose (21), glucose (22), and myo-inositol (25) were relatively higher in Cornaceae than in Fabaceae and Rosaceae. The fruits of C. mas have been reported as containing significant proportions of organic acids (4.6-7.4 %) and gallic acid was identified (Deng et al 2013). Gallic acid is a known precursor of hydrolysable tannin, which is synthesized from an intermediate precursor named dehydroshikimic acid (Ossipov et al 2003).…”
Section: Metabolic Pathway Correlations and The Relative Contents Of mentioning
confidence: 99%